Comparative Study on Various Modified Epoxy for Fiber Reinforced Polymer Strengthening Concrete Structure - Mohd Fauzi, Syasya Sahira; Abdullah, Siti Radziah (Recent Trends in Civil Engineering and Built Environment, 2024)
Epoxy has been used as adhesive in Fiber Reinforced Polymer (FRP) strengthening systems for upgrading concrete structures all over the world. The most common type of epoxy is cold-cured epoxy resin which hardens and achieves considerable mechanical properties at ambient temperature. However, uncertainty occurs when it is applied to structures whereby the durability of the material will be an issue, therefore, modifications of epoxy are required to toughen the epoxy to suit the purpose of repairing a concrete structure. Hence, this research involves an investigation and comparison of various materials replacement such as quarry dust, rice husk ash (RHA), as well as waste glass powder to modify epoxy resin in terms of compressive and bond strength. By comparing the results collected from the previous study, the optimum value of materials replacement used in the samples which could improve compressive and bond strength would be found. The comparison and analysis were done by using basic statistical analysis which is mean, standard deviation, correlation, and regression. All of these statistical analyses were calculated and the results were generated in Microsoft Excel. Based on the analysis, it could be concluded that RHA consists of the highest value of compressive strength recorded which is 59.3MPa with 5% of RHA content in a sample. As for the bond strength investigated, quarry dust record the highest value of bond strength which is 3.565MPa with 15% of quarry dust content in a sample.